The diversity of Polychaeta in the Kaca-kacu waters of the Pulau Nasi, Aceh Besar district - Sarah Nadia; Ali Sarong; Ismul Huda; Mimie Saputri; Devi Syafrianti (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
This study is entitled "Polychaeta Diversity in the Glass-kacu Waters of Nasi Island, Pulau Aceh District, Aceh Besar Regency". Polychaeta is a worm that belongs to the Phylum Annelida which has a setae, a broad body, so that its cosmopolitan life in various types of marine ecosystems. The purpose of this study, to determine the level of diversity of Polychaeta species found in the Glass-Kacu Waters and to determine the physical-chemical environmental conditions. The method used survey method with purposive sampling technique based on the presence of Polychaeta in the waters. Data analysis uses the Shannon-Winner diversity index formula, analyzed descriptively and displayed in tables. The results of the study were 10 species of Polychaeta from 5 families. The level of diversity of Polychaeta which is located at two stations in the waters of Pulau Nasi, Pulau Aceh District, Aceh Besar Regency is classified as low with diversity index adalah = 1.3158. The species that dominates in the Glass-kacu waters is Spirobranchus giganteus. For the measurement of physics-chemical factors for temperatures ranging from 24 0C-28 0C, pH 7.0 to 8.17, and 300/00-320/00. Keywords: Polychaeta Diversity, Cosmopolitan Penelitian ini berjudul “Keanekaragaman Polychaeta di Perairan Kaca-kacu Pulau Nasi Kecamatan Pulau Aceh Kabupaten Aceh Besar”. Polychaeta adalah cacing yang termasuk dalam Filum Annelida yang memiliki setae, tubuh beruas-ruas hingga penuh kosmopolitan di berbagai tipe ekosistem laut. Tujuan penelitian ini, untuk mengetahui tingkat populasi spesies Polychaeta yang terdapat di Perairan Kaca-Kacu serta untuk mengetahui faktor-faktor lingkungan fisika-kimia. Metode yang digunakan metode survei dengan teknik pengambilan sampel menggunakan Purposive Samplingberdasarkan penyelesaian Polychaeta di perjalanan. Analisis data menggunakan rumus indeks variasi Shannon-Winner, dianalisis secara deskriptif dan diselesaikan dalam bentuk tabel. Hasil penelitian Ada 10 spesies Polychaeta dari 5 famili. Tingkat keragaman Polychaeta yang bergantung pada dua stasiun di Kawasan Perairan Pulau Nasi Kecamatan Pulau Aceh Kabupaten Aceh Besar di katogorikan rendah dengan indeks keanekaragamannya adalah Ĥ = 1,3158. Spesies yang menentang di daerah Perikanan Kaca-kacu adalah Spirobranchus giganteus . Untuk Pengukuran faktor fisika-kimia untuk review Suhu berkisar 24 0 C-28 0 C, pH 7,0- 8,17, Dan 30 0 / 00 -32 0 / 00 .Kata Kunci: Keanekaragaman Polychaeta, Kosmopolitan